INTEGRATING BIM WITH 3D WEB DESIGN FOR ENHANCED 3D BUILDING VISUALIZATION AND SAFETY PLANNING IN CONSTRUCTION PROJECTS - I Made Surya Kumara; I Kadek Agus Wahyu Raharja; Harry Chan (Master Program of Infrastructure and Environmental Engineering, Postgraduate Program, Warmadewa University, 2024)
The construction industry is renowned for its hazardous nature, with a significant number of accidents occurring annually. These accidents result in serious consequences, including costs for disability benefits, decreased worker productivity, and idle equipment, hindering development. To address these challenges, safety must be a priority during the construction planning stage. Occupational Health and Safety (OSH) programs play a crucial role in ensuring worker safety and health. Building Information Modeling (BIM) has emerged as a technology that can significantly improve safety in construction projects. BIM provides detailed information and visualizations that help identify potential hazards and develop effective mitigation strategies. However, its implementation in Indonesia is still limited to level 1 BIM, primarily involving 2D and 3D CAD drafting. To enhance 3D building visualization and safety planning, this paper proposes integrating BIM with three.js and ReactJS. Three.js is a JavaScript library that enables the creation of 3D visualizations in web browsers, while ReactJS is used to build user interfaces in web applications. By combining these technologies, interactive web applications can be developed to display 3D buildings in real-time. This allows users to easily view building designs, identify potential hazards, and make informed decisions regarding safety measures. Furthermore, the Industry Foundation Classes (IFC) file format is utilized for data exchange in the BIM environment. IFC contains building geometry information, material properties, and other relevant data, enabling collaboration among project teams using different software. This integration enhances collaboration and facilitates more informed decision-making in construction projects. The results demonstrate efficient 3D rendering of BIM models with an average response time of 0.8 seconds, as well as real-time visualization of worker positions within buildings based on sensor data.